NONSUICIDAL SELF-INJURY IN OLDER VERSUS MIDDLE-AGED/YOUNGER VETERANS SEEKING TREATMENT FOR POSTTRAUMATIC STRESS. (16th November 2018) - Gregg, J; Deming, C; Libman, C; Clancy, C; Calhoun, P; Beckham, J; Kimbrel, N
Abstract: Nonsuicidal self-injury (NSSI) refers to the act of purposefully damaging one's body tissue without suicidal intent for reasons that are not socially sanctioned (Klonsky, 2011). Research on NSSI has demonstrated that it is strongly associated with suicidal behavior, including suicidal ideation, suicide attempts, and deaths by suicide (e.g., Nock et al., 2017; Kimbrel et al., 2017). Despite overall increases in emotion regulation with age, older adults are disproportionately affected by suicide; however, little, if any, research has examined NSSI among older adults to date. In our study, we examined the frequency and correlates of NSSI among older versus middle-aged/younger adults in a sample of 1, 136 veterans seeking treatment for posttraumatic stress (134 ≥ 60 years old). Lifetime NSSI was prevalent in our sample (81.9%), but significantly lower in older versus younger adults (67.9% and 83.7%, respectively, p<.001). Likewise, recent NSSI (within the past two weeks) was prevalent (64.3%), but significantly lower among older veterans (52.2% and 66.0%, p<.01). There were no differences between older and younger adults regarding recent engagement in scratching, self-hitting, or burning. However, significant differences were observed regarding recent wall/object punching (29.1% vs. 45.1%) and cutting (1.5% vs. 5.5%, p<.05). As with younger adults, NSSI was significantly and positively associated with current suicidal ideation among older adults. Our results suggest that, while NSSI is less frequent among older versus younger treatment-seeking veterans, it remains quite prevalent and is related to increased suicide risk. Implications and future directions will be discussed.